SOUTH KOREA'S POLICY TOWARDS THE EUROPEAN UNION: MAIN STAGES, FEATURES AND DEVELOPMENT TRENDS (Journal of history, 2024)
The article examines the history of South Korea's policy towards the European Union since its formation. The purpose of the article is to study South Korea's policy towards European countries after gaining independence in 1948. It was important for South Korea to gain diplomatic recognition of independent European states. The article, based on South Korean and European materials, examines the policies of the presidential administrations of Rhee Syngman, Park Chung-hee, Roh Tae-woo, etc. The study used a descriptive method to capture the main points of interaction between South Korea and the EU countries. A realistic approach to international relations was used to analyze bilateral contacts between Seoul and Brussels, according to which states are primarily guided by their national interests when cooperating with other states. The study showed that Park Chung-hee, having become president of South Korea in 1962, intensified his foreign policy activities towards cooperation with developed Western European countries. He sought to attract investment into the economy, open the European market for South Korean business and isolate North Korea in the international arena. In the late 1980s, a thaw in the Cold War occurred on the international stage, which made it possible for South Korean President Roh Tae-woo to pursue his "Northern Policy" and establish contacts with the Soviet Union and Eastern European countries.The author came to the conclusion that after the end of the authoritarian period in South Korea, political, economic and humanitarian ties between Seoul and Brussels are strengthening and expanding. In addition, the article reveals the contractual and legal relations between the European Union and South Korea, as well as trade disputes between South Korean and European businesses.
Keywords: Republic of Korea, international organizations, EU, Europe.